Geriatric patients with acute kidney injury in the intensive care unit: the effect of vitamin B12 and albumin levels on survival - Erarslan, Sertaş; Paşalı Kilit, Türkan (The European Research Journal, 2025)
Objectives: Acute kidney injury (AKI) is a common and critically important clinical entity in geriatric age group. In addition, higher mortality rates are seen in cases requiring intensive care treatment. We have aimed to investigate the effect of vitamin B12 and albumin levels on mortality in critically ill geriatric patients with AKI. Methods: Geriatric patients hospitalised in the Intensive Care Unit with a diagnosis of AKI between 07.01.2014-07.01.2015 were retrospectively screened and included in the study. Two groups were formed from discharged and exited patients. General characteristics and laboratory values of the patients were scanned from the hospital archives and recorded. Statistically significant intergroup differences in terms of demographic characteristics, and biochemical values were determined by statistical analysis. Results: A total of 103 patients, including 53 females were enrolled in the study, while 72.2% of the patients had prerenal AKI. The mortality rate was 47.57% in all patients. There was no difference between groups in terms of mortality rates, etiologic factors and KDIGO staging. Vitamin B12 was high and albümin was low the group who succumbed to death. In addition, mortality rates increased by 10% for every 100 units increase in vitamin B12 value and decreased by 22% for every 10 units increase in albumin value. Conclusions: We have determined that an increase in albumin levels during clinical follow-up decreased mortality rates and an increase in vitamin B12 levels directly increased mortality rates. Hypoalbuminemia and high vitamin B12 levels were found to be independent predictive factors for mortality in AKI.